Efficient extraction of sulfate from water using a Zr-metal–organic framework. Issue 1 (24th November 2015) - Howarth, Ashlee J.; Wang, Timothy C.; Al-Juaid, Salih S.; Aziz, Saadullah G.; Hupp, Joseph T.; Farha, Omar K.
Abstract : A Zr-based metal–organic framework, NU-1000, is used to extract sulfate from aqueous solutions containing competitive anions. This is of interest for application in the safe disposal and storage of nuclear waste where sulfate anions are known to interfere with the waste vitrification process. Abstract : A Zr-based MOF, NU-1000, comprised of Zr6 nodes and tetratopic pyrene-containing linkers is studied for adsorption and extraction of SO4 2− from water. The adsorption capacity and uptake time of SO4 2− in NU-1000 is determined at varying concentrations to give an overall maximum adsorption capacity of 56 mg SO4 2− per g of MOF. Selective adsorption of SO4 2− by NU-1000 in the presence of other anions as well as regeneration of the sorbent is also explored.